125I seeds inhibit proliferation and promote apoptosis in cholangiocarcinoma cells by regulating the AGR2-mediated p38 MAPK pathway. (1st January 2022) - Zhou, Xueliang; Zhang, Wenguang; Dou, Mengmeng; Li, Zhaonan; Liu, Zaoqu; Li, Jing; Tian, Chuan; Yao, Yuan; Wang, Chaoyan; Li, Yahua; Chen, Pengfei; Han, Xinwei; et al.
Abstract: 125 I seeds can effectively inhibit the growth of a variety of cancer cells. It has been used in the treatment of a variety of cancers, and has achieved certain curative effect. However, to the best of our knowledge, no report has described the effects of 125 I seeds on the biological functions of cholangiocarcinoma (CCA) and the mechanisms underlying the effects of the seeds on this cancer. In this study, we demonstrated that 125 I seeds could inhibit the proliferation, migration and invasion of CCA cells, as well as promoting apoptosis and blocking the cell cycle in these cells. Moreover, 125 I seeds inhibited the growth of CCA xenografts and promoted the apoptosis of CCA cells in vivo . Furthermore, transcriptome sequencing showed that 125 I seeds could inhibit the growth of CCA by inhibiting the expression of AGR2 and regulating p38 MAPK pathway. Finally, this finding indicated that 125 I seeds can inhibit proliferation and promote apoptosis in CCA cells by inhibiting the expression of AGR2 and DUSP1 and increasing the expression of p-p38 MAPK and p-p53. This study provides a new research direction for studies investigating the mechanisms underlying the effects of 125 I seeds on CCA. Highlights: This study demonstrated for the first time that 125 I seeds could inhibit the proliferation, migration and invasion of cholangiocarcinoma cells QBC939 and RBE, as well as promoting apoptosis and blocking the cell cycle in these cells. Furthermore, transcriptome sequencing for the first time showed that 125 I seeds could inhibit the growth of cholangiocarcinoma by inhibiting the expression of AGR2 and regulating p38 MAPK pathway. This study clarified for the first time that 125 I seeds can inhibit proliferation and promote apoptosis in cholangiocarcinoma cells by inhibiting the expression of AGR2 and DUSP1 and increasing the expression of p-p38 MAPK and p-p53.